The role of collective angst during and after a service failure. Issue 3 (6th May 2014) - A. Maher, Amro; Sobh, Rana
Abstract : Purpose: – The purpose of this study is to examine the role of collective angst, the concern about the future viability of one's group, during service failure and recovery. Design/methodology/approach: – To test this objective the authors utilize an experiment to examine how Kuwaitis react to service failures when the front-line employee is a foreigner. Findings: – The results indicate that collective angst is associated with greater anger following a service failure. The authors also find that collective angst moderates the impact of cultural distance on anger and recommendation intentions following a service-failure recovery attempt. More specifically, cultural distance leads to greater anger and lower intentions to recommend a service establishment for consumers that experience greater collective angst. Originality/value: – The research provides the first attempt at examining how local consumers react to foreigner service providers, by examining how concern about the future vitality of one's national group, in other words collective angst, affects such reactions.